2018
DOI: 10.2489/jswc.73.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of edge-of-field monitoring of agricultural runoff in addressing nonpoint source pollution

Abstract: While basin-scale studies and modeling are important tools in relating land uses to water quality concerns, edge-of-field monitoring (EOFM) provides the necessary resolution to spatially target, design, and evaluate in-field conservation practices for reducing nonpoint source pollution from agriculture. This paper introduces this special issue of the Journal of Soil and Water Conservation, a collection that provides an overview of EOFM on agricultural lands. The issue describes the transition of EOFM from a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Further, measuring P losses from a single spatial scale while providing information on local source and transport factors does not allow for assessment of P transport beyond the plot or field. Nested water quality monitoring studies (i.e., monitoring across spatial scales or fields within watersheds) can be useful for understanding how both biogeochemical (source) and hydrologic (transport) factors influence downstream nutrient losses (Bauwe et al., 2015; Daniels et al., 2018; Lohani et al., 2020) and for assessing watershed P buffering capacity (Kusmer et al., 2019). Identifying nutrient sources and evaluating the impact of upland management practices on downstream loading are essential for increasing the efficacy of conservation practice implementation (Williams et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further, measuring P losses from a single spatial scale while providing information on local source and transport factors does not allow for assessment of P transport beyond the plot or field. Nested water quality monitoring studies (i.e., monitoring across spatial scales or fields within watersheds) can be useful for understanding how both biogeochemical (source) and hydrologic (transport) factors influence downstream nutrient losses (Bauwe et al., 2015; Daniels et al., 2018; Lohani et al., 2020) and for assessing watershed P buffering capacity (Kusmer et al., 2019). Identifying nutrient sources and evaluating the impact of upland management practices on downstream loading are essential for increasing the efficacy of conservation practice implementation (Williams et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that individual and combinations of best practices can mitigate erosion and surface runoff nutrient loss potential. Much of this is from field plots, however, which largely ignores the dynamic nature and complex hydrology of larger fields/watersheds [31][32][33]. Evaluating the effectiveness of practices at the landscape and watershed scales is also challenging due to the heterogeneity of runoff processes [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the effectiveness of practices at the landscape and watershed scales is also challenging due to the heterogeneity of runoff processes [34][35][36]. Paired watershed designs account for inherent physiographic differences between watersheds and can help to isolate management effects on runoff water quality [9,32,37,38]. The objective of this study was to use a paired-watershed approach to quantify the effectiveness of targeted BMPs to mitigate surface runoff nutrient transport from corn silage fields in central Wisconsin (WI) with high runoff potential.…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar equipment system, Daniels et al. (2018) showed effectiveness of grassed waterways on flow, total P, and total N reductions. An edge‐of‐field monitoring study in Arkansas showed significantly greater losses of sediment and nutrients during non‐crop periods (Reba et al., 2020), suggesting the effectiveness of continuous cover and other conservation practices.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, since participation among landowners was voluntary, monitoring locations were largely a function of willingness to partner and the successful acquisition of a MRBI contract with the USDA‐NRCS. Recently, edge‐of‐field monitoring has received increasing attention during the last decade in evaluating the effectiveness of conservation practices on water quality of agricultural runoff (Daniels et al., 2018). The data collected can be effectively used to evaluate conservation performance, simulate watershed models to quantify long‐term benefits, and for on‐farm adaptive management at a fine resolution.…”
Section: Introductionmentioning
confidence: 99%